Leveling Up Junior High School Students' Critical Thinking Skills: Mathematical Thinking Patterns through Polya's Theory - Fathrul Arriah; Ilhamuddin Ilhamuddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This research is prompted by junior high school pupils' low mathematical critical thinking skills in tackling non-routine situations. Students generally struggle with solution formulation and planning, indicating poor systematic and logical thinking. This study examines Junior High School 1 Bulukumba students' mathematical critical thinking skills in solving mathematical problems using Polya's Theory's four steps: Understanding the Problem, Planning a Solution, Implementing the Plan, and Looking Back. Grade VIII pupils of Junior High School 1 Bulukumba are the participants of this qualitative descriptive study. The study collects data through problem-solving tests based on non-routine issues, observation, and in-depth interviews. The results of the study indicate that most research subjects have been able to carry out Stage 1 (Understanding the Problem) well. However, significant weaknesses were identified in Stage 2 (Planning a Solution), where students have not been able to formulate appropriate and coherent strategies, and Stage 4 (Looking Back), where students tend to ignore validation and rechecking answers. A mechanistic approach without reflection still dominates students' critical mathematical thinking. This research helps teachers and schools diagnose pupils' critical thinking skills. These findings can be utilized to construct learning interventions that improve strategic planning and self-evaluation (reflection) skills in problem-solving contexts to